METABOLIC ADAPTATION STRATEGY USING Zymomonas mobilis CP4 CELLS FOR THE PRODUCTION OF SECOND GENERATION ETHANOL - Martins, Danielle da Silveira dos Santos; Borges, Elcio Ribeiro; Reis, Viviane Castelo Branco; Torres, Fernando Araripe Goncalves; Jr, Nei Pereira (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2015)
During the past few decades, considerable effort has been made to utilize agricultural and forest residues as biomass feedstock for the production of bioethanol as an alternative fuel. The bacterium Zymomonas mobilis was shown to be extremely attractive for the production of second-generation ethanol from glucose of the cellulose fraction due to its ability to uptake high amounts of this sugar, resulting in high ethanol productivity values. However, the wild-type strains are unable to metabolize xylose that arises from the hemicellulose fraction. Molecular biology techniques were incorporated to render the strain used in this study capable of fermenting xylose into ethanol and thus increase the efficiency of second-generation ethanol production. Thus, the aim of this study was to evaluate the performance of a recombinant strain of Z. mobilis in simultaneous saccharification and co-fermentation (SSCF) processes, in which the fermentation of both sugars (glucose and xylose) occurs in one step. Regarding the genetic transformation,the 1,565 kb Z. mobilis plasmid pZMO1 was chemically synthesized and cloned into a synthetic vector that contains the E. coli and Z. mobilis replication checkmark origin,the XI, XK, TAL, and TKL genes and tetracycline resistance. Metabolic adaptation was performed by transferring the recombinant strain to media containing increased xylose concentrations. Then, an experimental response surface methodology was used to evaluatethe addition of glucose and xylose with different concentrations, as well as the incorporation of hemicellulosic hydrolyzate in different proportions. The recombinant Z. mobilis CP4 strain reached 25 g/L ethanol, confirming that approximately 50% of this pentose was consumed in the SSCF process when using 30% solids, 20.5% hemicellulose hydrolysate, 10 mg/L tetracycline, an enzyme load of 25 FPU/g cellulignin, and 10% of the initial inoculum.